Exciton Dynamics and Effects of Structural Order in Morphology‐Controlled J‐Aggregate Assemblies. (20th December 2018) - Anantharaman, Surendra B.; Stöferle, Thilo; Nüesch, Frank A.; Mahrt, Rainer F.; Heier, Jakob
Abstract: Narrow‐band photoluminescence (PL) together with high quantum efficiency from organic molecules is essential for high‐color‐purity emitters. Supramolecular assemblies like J‐aggregates are promising materials due to their narrow PL signal with full‐width at half maximum <20 nm. However, their microcrystalline nature and coherent exciton migration results in strong nonradiative exciton recombination at the grain boundaries that diminish the photoluminescence quantum yield (PLQY), and possibilities for improving the crystallinity by tuning the growth mechanism are limited. Here, two distinct routes to grow different J‐aggregate morphologies like platelets and lamellar crystals with improved crystallinity by surface‐guided molecular assembly are demonstrated, thereby suppressing nonradiative decay and improving PLQY. Both platelets and lamellar crystals show similar absorbance at room temperature. However, temperature‐dependent PL studies show sevenfold (twofold) higher PLQY for lamellar films compared to platelets at 6 K (300 K). Using time‐resolved PL spectroscopy, different nonradiative decay pathways are identified. The dependence of exciton diffusion on energetic disorder and nonradiative decay is discussed. The results suggest that the difference in domain size and order gives rise to significantly enhanced radiative decay from lamellar films as compared to platelets or films formed by spin‐coating. Abstract : Narrow‐band photoluminescence (PL) from supramolecular assemblies is nonradiatively quenched by grain boundary annihilation. Here, it is shown that excess energy through optical excitation can foster exciton dissociation. Exciton‐charge quenching is then an additional nonradiative decay channel that decreases the PL. Growing high‐quality crystals and reducing the number of grain boundaries can obviate nonradiative quenching processes to significantly enhance the PL.